Navigating the Social Environment: Linking Motivations, Impressions, and Behaviors Via a Sampling Approach to Trustworthiness. - Biella, Marco; Hütter, Mandy (Personality & Social Psychology Bulletin, 2026)
Our understanding of impression formation comes from experiments constraining participants' control over information sampling. This limits our understanding of how people sample information when forming impressions as well as the effects of self-generated samples on impressions. Our paradigm allows participants to actively collect information samples. This work investigates how people explore the social environment and how sampled information informs resulting impressions. Four experiments tested theoretically-driven predictions regarding information sampling patterns under interested and disinterested information search. Under interested search, participants truncated the sampling of social targets showing early untrustworthy behavior. Under disinterested search, participants sampled extensively and systematically, avoiding small-sample biases. The sampled information, once obtained, accurately determines final impressions. Moreover, we documented a direct link between sampled information and subsequent behaviors (partner selection in trust games, trustworthiness expectations). By investigating sampling-based trustworthiness impressions, the present research informs the origins of trustworthiness and sampling accounts of judgment and decision-making.